Beyond the Exam Room: Teaching Intervisit Care to Internal Medicine Residents - Matthew J. Mulligan; Amanda B. Breviu; Sarah K. Hall; Karen E. Stenehjem; Anne C. Cioletti (MedEdPORTAL)
Introduction Intervisit care, asynchronous care provided between patient visits, represents an essential part of patient care. Despite the importance of intervisit care, residency programs have not traditionally taught residents how to effectively manage intervisit care within the formal curriculum. We aimed to improve resident preparedness in providing intervisit care with an intervisit workshop. Methods We developed a 2-hour, small-group, interactive workshop on intervisit care for categorical internal medicine interns at the University of Utah in Fall of 2023. The workshop consisted of a didactic session introducing a novel framework for intervisit care medical decision-making, case-based application, and practical site-specific applications using the electronic health record. We evaluated the workshop with an electronic survey following the session. Results Thirty-two internal medicine residents (100% participation rate) participated in the workshop and 26/32 (81%) completed the survey. Residents felt intervisit care education was extremely important (median = 5, interquartile range [IQR] = 1). Residents felt more prepared to provide intervisit care after the workshop (median = 2, IQR = 2, vs. median = 4, IQR = 0; p < .001). Residents felt the framework for medical decision-making was helpful (median = 4, IQR = 1). Discussion By employing a framework to guide medical decision-making and guided application, our intervisit care workshop improved residents’ perceived preparedness in providing intervisit care for their patients. This workshop addresses a major gap in medical education and can be adapted by other institutions and specialties. Further work is needed to reinforce content and develop metrics of intervisit care.